Idempotent Divisor Graph of Commutative Ring: Idempotent Divisor Graph - Mohammad, Husam Q.; Shuker, Nazar H. (Iraqi Journal of Science, 2022)
This work aims to introduce and to study a new kind of divisor graph which is called idempotent divisor graph, and it is denoted by . Two non-zero distinct vertices v1 and v2 are adjacent if and only if , for some non-unit idempotent element . We establish some fundamental properties of , as well as it’s connection with . We also study planarity of this graph.